Exploring Students' Perspectives on the Use of Grammarly in Writing Analytical Exposition Text - Inayah, Tarisa Marta; Apoko, Tri Wintolo (Universitas Islam Ahmad Dahlan (UIAD), 2024)
This study explores the students' perspectives of Grammarly and its effectiveness in improving their writing skills. Using a mixed methods approach with 60 participants (53% male, 47% female), the research collected quantitative data through a questionnaire distributed via Google Form and qualitative data through interviews with nine students. Integrating quantitative and qualitative findings revealed a generally positive view of Grammarly. Quantitative findings show that 63% of students found Grammarly useful, and 72% agreed that Grammarly feedback significantly improved their writing quality. Additionally, 52% of students appreciated detailed feedback, and 63% reported that Grammarly helped them better understand grammar rules. In relation to the perceived use of ease, the study revealed that 55% of students found Grammarly easy to use, and 61% agreed that Grammarly provided clear feedback on errors. Qualitative data confirms these findings, highlighting Grammarly's effectiveness in correcting mistakes, enhancing grammar understanding, and increasing students writing confidence. Students also valued Grammarly as being easy to use and allowing them to simplify the writing process, save time, and make writing tasks more manageable. However, some of Grammarly's advanced features require a paid premium subscription, which may be an obstacle for some users. The study concludes that integrating technology with Grammarly in EFL writing instruction offers significant benefits, including increased confidence in writing, better understanding of Grammarly, and efficient feedback.